Histological and proteomic profile of diabetic versus non-diabetic dilated cardiomyopathy. (15th January 2016) - Frustaci, Andrea; Ciccosanti, Fabiola; Chimenti, Cristina; Nardacci, Roberta; Corazzari, Marco; Verardo, Romina; Ippolito, Giuseppe; Petrosillo, Nicola; Fimia, Gian Maria; Piacentini, Mauro
Abstract: Background: Diabetic cardiomyopathy (DbCM) is indistinguishable from idiopathic dilated cardiomyopathy (IDCM) as specific histological and/or biochemical markers are unavailable. Methods and results: Comparative histology, electron microscopy, morphometry for cell volume composition and myocardial fibrosis, reactive oxygen species (ROS), polymerase chain reaction for cardiotropic viruses, immunohistochemistry for nitrotyrosine, inducible nitric oxide synthase (iNOS), 8-hydroxydeoxyguanosine (8-OH-dG) and proteomics have been evaluated in endomyocardial biopsies from 9 patients (pts) (5 male and 4 female, mean age 61 ± 13 years) with DbCM (left ventricular end-diastolic diameter 65 ± 2.3 mm; ejection fraction 27 ± 6) and type 2 diabetes mellitus and 9 pts with IDCM (mean age 60 ± 9 years) matched for sex, age and severity of left ventricular (LV) dysfunction. Controls were surgical biopsies from 9 pts with mitral stenosis and normal LV dimensions and function. No qualitative morphological changes were observed between DbCM and IDCM although mitochondrial damage and myofibrillolysis appeared more pronounced in DbCM. ROS were 5 times higher in DbCM than in IDCM and controls and were associated with higher expression of cytoplasm iNOS and nitrotyrosine and nuclear 8-OH-dG. Apoptosis was 14 times higher in DbCM than in IDCM and 41 times higher than in controls. Proteomic profile showed in DbCM a reduced expression of proteins related to beta-oxidation and detoxification pathway. Conclusions: DbCM is a distinctive ROS-mediated disorder with oxidative damage of myocyte's structural proteins and DNA causing cell dysfunction and death. Reduced expression of beta-oxidation proteins suggests a decline of energy production and of mitochondrial function. Highlights: Diabetic cardiomyopathy (DbCM) is indistinguishable from idiopathic dilated cardiomyopathy (IDCM). Definition of pathophysiology and markers of DbCM is highly desirable. Morphology, proteomics and reactive oxygen species (ROS) production are evaluated in DbCM vs IDCM. DbCM is a ROS-mediated damage of myocyte's structural proteins and DNA